FAMILY BUSINESS AND THEIR CONCERN TO CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Rahman Anshari; Ermi Utami (Universitas Muhammadiyah Kalimantan Timur, 2021)
The purpose of this study is to empirically examine the effect of a family business on the disclosure of Corporate Social Responsibility. The sample in this study is a company that can be identified as a family company in a manufacturing company listed on the Indonesia Stock Exchange in 2017 – 2019. The number of samples in this study is 99 samples. This study divides the family business into two variables: the family as the first largest shareholder and the family as the second-largest shareholder. The variable of family ownership as the first largest shareholder is measured using a dummy variable, given a value of 1 if the family is the first largest shareholder and 0 otherwise. The variable of family ownership as the second-largest shareholder is measured using a dummy variable, given a value of 1 if the family is the second-largest shareholder and 0 if other. CSR disclosure variable is measured using the disclosure index. The first control variable is the firm size measured using the natural logarithm of total assets. The second control variable is the firm age measured using years the firm was found until years of the research. Data were analyzed using multiple regression. The results showed that the family as the first largest shareholder and the family as the second-largest shareholder had no significant effect on corporate social responsibility disclosure.